THE EFFECT OF CORPORATE GOVERNANCE ON ACCOUNTING INFORMATION QUALITY (Survey on Publicly Listed Companies in Indonesia Stock Exchange 2011-2016) - Judith T.G. Sinaga (Program Studi Magister Manajemen Universitas Advent Indonesia, 2018)
This research is conducted to know the current situation of Indonesia’s corporate governance and accounting information quality. Good corporate governance is one of the aspects that should be considered to obtain accounting information quality. Good corporate governance was measured by using corporate governance perception index (CGPI) while accounting information quality was measured using discretionary accruals (Jones Model). The result showed that good corporate governance has a significant effect on accounting information quality. Companies that practice good governance will eventually produce accounting information with quality.